Effects of weathered polyethylene microplastic ingestion on sexual maturation, fecundity and egg quality in maturing broodstock Atlantic cod Gadus morhua. (1st March 2023) - Fernández-Míguez, M.; Puvanendran, V.; Burgerhout, E.; Presa, P.; Tveiten, H.; Vorkamp, K.; Hansen, Ø.J.; Johansson, G.S.; Bogevik, A.S.
Abstract: Microplastics (MPs) have become a global issue as they are omnipresent in the ocean. Fish ingesting MPs through feed could be affected in their physiological function, e.g., disrupted enzyme production and function, reduction of feeding and reproductive failure. This study assessed the effects of feed containing naturally weathered MPs from the Oslofjord (Norway) on the reproductive physiology of Atlantic cod ( Gadus morhua ). Farmed cod broodstock were fed either control (C-diet) or feeds containing 1% microplastic (MP-diet) starting nine months prior to spawning, from June until May. No major differences were found between diet groups in overall biometrics or gonad histology. Sex steroid levels (testosterone, 11-ketotestosterone and 17β-estradiol) resulted in expected profiles increasing over time without any significant differences between treatments. Gene expression levels of the steroidogenic enzyme 20β-hydroxysteroid dehydrogenase ( 20β-hsd ) and vitellogenin1 ( vtg1 ) showed significant differences between dietary treatments with lower expression in the control group. This can be a direct effect of MPs, but endocrine disrupting effects of potentially leachable plastic additives cannot be completely ruled out. Thus, these enzymes could be indicators of exposure to contaminants that disrupt sexual maturation by affecting the production of primarily maturation-inducing steroid. Although the concentration of MPs employed in this study may not be high enough to elicit any observable short-term biological effects, the observed gene expression suggests that long-term consequences should be considered caused by an expected increase of MPs in marine environments. Graphical abstract: Image 1 Highlights: Dietary inclusion of 1% weathered PE had no effect on digestion or fish biometrics. No dietary effect on gonadal development, fecundity or on egg quality were observed. Gene expression through the BPG-axis and plasma steroid analysis was normal. Gonadal and liver gene expressions of 20β-hsd and vtg1 differed between the groups.